The Binding Efficiency and Interaction of Lactobacillus casei Shirota Toward Aflatoxin B1 - Liew, Winnie-Pui-Pui; Nurul-Adilah, Zainuddin; Than, Leslie T. L.; Mohd-Redzwan, Sabran (Frontiers in Microbiology, 2018)
The use of probiotic as dietary approach to prevent exposure to food contaminant, aflatoxin B1 (AFB1) has greatly increased. Several studies found that AFB1 binding to the bacterial cell wall is a strain-specific. Moreover, the interaction between AFB1 and bacterial cell wall is not well-understood, thus warrants further investigation. This research was conducted to assess the ability of Lactobacillus casei Shirota (Lcs) to bind AFB1 at different concentrations and to determine AFB1 binding efficiency of different Lcs cell components including live cell, heat-treated, and cell wall. In addition, the interaction between AFB1 and Lcs was also evaluated via scanning electron microscopy (SEM) and through an animal study. The binding of AFB1 by all Lcs cell components depends on the concentration of available AFB1. Among all Lcs cell components, the live Lcs cells exhibited the highest binding efficiency (98%) towards AFB1. Besides, the SEM micrographs showed that AFB1 induced structural changes on the bacterial cell surface and morphology including rough and irregular surface along with a curve rod-shaped. In vivo experiment revealed that Lcs is capable to neutralize the toxicity of AFB1 on body weight and intestine through the binding process. The animal’s growth was stunted due to AFB1 exposure, however, such effect was significantly (p<0.05) alleviated by Lcs. This phenomenon can be explained by a significant (p<0.05) decreased level of blood serum AFB1 by Lcs (49.6±8.05 ng/mL) compared to AFB1-exposed rats without treatment (88.12±10.65 ng/mL). Taken together, this study highlights the potential use of Lcs as a preventive agent against aflatoxicosis via its strong binding capability.